Korelasi dan Analisis Koefisien Lintas Karakter Tandan Bunga Terhadap Buah Jadi Kelapa Genjah Salak - MIFTAHORRACHMAN MIFTAHORRACHMAN (Buletin Palma, 2010)
Correlation and Path Coefficient Analysis of Bunch Character on Fruit Set of Salak Dwarf Coconut The research was conducted to investigate the correlation among six flowering characters of Salak Dwarf coconut and also to asses their direct and indirect effects which will be used for the selection of fruitset and fruit production. Six characters of Salak Dwarf flowering were evaluated at Kima Atas experimental garden, Manado, North Sulawesi, during 2009. Those were, number of female flower per bunch, Number of spikelet per bunch, weight of male flower per bunch, weight of polen per bunch, pollen viability, and number of fruit set per bunch. Minitab program was used to quantify the Coefficient correlation, while measuring of path coefficient based on Singh and Chaudary. The result showed that number of female flower and number of spikelet had the highest direct significant effect to fruit set, whereas, path indirect effect was showed by weight of pollen via number of female flower.